Waste cooking oil (WCO) collection center location in Seremban 3 by using AHP / Amirah Rusdah Zulkifli, Nurfarhana Ab Wahid and Salwa Nur Ain Suhaili - Zulkifli, Amirah Rusdah; Ab Wahid, Nurfarhana; Suhaili, Salwa Nur Ain (2023)
The current rise in population density, the consumption of oil in food preparation, resulted in a massive volume of waste cooking oil (WCO) production worldwide either from household or commercial activities. Low of awareness in disposing of WCO may contribute to water and soil contamination, disrupt aquatic life, cause sewer system blockages and overflows, raise water treatment and waste management costs, and have unfavourable consequences for the entire environmental system. The aims of this study are to identify household attitudes and practices towards WCO recycling by conducting online surveys and establish the preferred WCO collection center for householders in Seremban 3, Negeri Sembilan using the Analytic Hierarchy Process (AHP) method. The AHP is a one of the multi-criteria decision-making tools, that is a math and psychology-based system for organizing and evaluating complicated choices. For this study, four (4) Criteria’s were considered in choosing the preferable WCO collection center location such as transportation cost, distance, facilities and responses. Regarding that Criteria’s, five (5) alternatives were identified which are Shell (A1), Family Store (A2), PETRONAS (A3), UiTM Seremban 3 (A4) and UniCITY Square (A5). By ranking the WCO Collection Center based on the criteria, the preferred locations among the alternatives can be achieved. As a result, household will be able to improve their decision-making skills and select the best place of choosing WCO collection center location.